Method for preparing few-layer large-area graphene by chemical vapor deposition and transferring thereof
Patent Information
- Application Number
- CN202311321949.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-13
AI Technical Summary
该方法采用化学气相沉积(CVD)的方法,以铜箔为衬底,甲烷为碳源,氢氩混合气体为载气,通过使生长温度高于铜箔融化温度,铜箔融化温度为1084℃,利用液态铜的准光滑和流变表面,解决因铜晶界处存在不均匀成核和不可控碳沉淀的缺点,导致石墨烯晶粒质量低,尺寸小且层数不均匀等问题
[0031]本发明中,首先在1100℃~1200℃下将铜箔熔融,然后通过化学气相沉积的方法在液态铜箔衬底上生长石墨烯。
Smart Images

Figure CN117364054B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of graphene material growth. It relates to a method for preparing and transferring few-layer, large-area graphene using chemical vapor deposition under ambient pressure. Background Technology
[0002] Graphene is a hexagonal honeycomb lattice structure composed of a single layer of carbon atoms. Its electronic structure is unique, with six vertices in the Brillouin zone (Dirac points, also known as K-points). Its conduction and valence bands are symmetrical around the Dirac points, and at the K-points, the band structure and wave vector of graphene exhibit a linear relationship. This unique lattice and electronic structure endows graphene with numerous excellent physical and electrical properties, including high mobility, high transmittance, high mechanical strength, and a large specific surface area. Therefore, graphene has become an excellent material for fabricating flexible displays and optoelectronic devices. Currently, graphene preparation methods include mechanical exfoliation, redox methods, silicon carbide epitaxial growth, chemical vapor deposition (CVD), and redox methods, among which CVD produces graphene with uniform layer count, low cost, and good quality.
[0003] In recent years, graphene has been successfully fabricated on various metal substrates, particularly copper substrates, using chemical vapor deposition (CVD). Due to the unique "self-limiting growth" mechanism of copper foil substrates, graphene can be easily obtained on them. Currently, traditional CVD methods for graphene preparation involve growing graphene on solid copper using a hydrogen-argon mixture as the carrier gas and methane as the carbon source. However, this approach still faces several challenges. Inhomogeneous nucleation and uncontrollable carbon precipitation at copper grain boundaries result in low grain quality, uneven graphene layer count, and the resulting graphene is typically a polycrystalline film, where grain boundaries reduce its excellent physicochemical properties. Therefore, growing graphene on solid copper requires very strict surface treatment. Our research aims to produce high-quality, uniform, and large-area graphene single crystals. While single-crystal metal substrates can achieve uniform monolayer graphene growth, they are expensive and have limited yields. Unlike solid substrates with rich surface morphologies, the quasi-smooth and rheological surfaces of liquid substrates offer an alternative and simpler method for producing high-quality, uniform graphene layers. Therefore, achieving the growth of large-sized, few-layer, high-quality graphene films on liquid copper foil substrates has become a key focus in the field of graphene materials. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of current technologies by providing a method for preparing and transferring few-layer, large-area graphene using chemical vapor deposition (CVD). This method employs CVD with copper foil as a substrate, methane as the carbon source, and a hydrogen-argon mixture as the carrier gas. By maintaining a growth temperature higher than the melting temperature of the copper foil (1084℃), the quasi-smooth and rheological surface of liquid copper is utilized to overcome the drawbacks of uneven nucleation and uncontrollable carbon precipitation at copper grain boundaries, which lead to low-quality, small-sized, and unevenly layered graphene. Furthermore, by adjusting the growth time and hydrogen-argon gas flow rate, a method for growing few-layer, large-area, high-quality graphene on a liquid copper foil substrate is developed. The graphene is then transferred from the copper foil surface to a Si / SiO2 substrate using a wet transfer method. Finally, graphene single crystals are prepared, and Raman spectroscopy reveals almost no defect peaks, demonstrating that the grown graphene possesses high crystallinity and significant application value.
[0005] The technical solution of this invention is as follows:
[0006] A method for preparing few-layer, large-area graphene using chemical vapor deposition, comprising the following steps:
[0007] S1. Clean the copper foil and tungsten foil with acetone, ethanol and deionized water respectively for 10-20 minutes, and then dry them with nitrogen gas.
[0008] S2. Place the copper foil on the tungsten foil, which serves as a support for the copper during melting. Place both foils in a quartz boat, push them into the heating zone of the tube furnace, and evacuate to 9-8.5E-1Pa.
[0009] S3. Under a mixed atmosphere, anneal at 1100℃~1200℃ and maintain the temperature for annealing for 30~40 minutes to make the copper foil molten.
[0010] The mixed atmosphere is hydrogen and argon, with a volume ratio of hydrogen to argon of 5-50:100-200.
[0011] The heating time is 55–65 minutes;
[0012] S4. Maintaining the atmosphere and temperature of the previous step, introduce CH4 gas into the tube furnace for 10 to 90 minutes; then turn off the CH4 gas and allow it to cool naturally to room temperature. A few-layer graphene film can be obtained on the copper foil substrate.
[0013] The CH4 flow rate is 1–5 sccm;
[0014] The minimum number of layers is 1 to 3 layers. Preferably, it is 2 layers.
[0015] The area of the graphene film is 0.25 cm². 2 ~1cm2 ;
[0016] The copper foil substrate described in S1 has a thickness of 250μm to 300μm.
[0017] The method for transferring the graphene film prepared by the method includes the following steps:
[0018] (1) PMMA was spin-coated onto a copper foil substrate with a graphene film deposited by a spin coater;
[0019] The spin coater parameters are: 1000-1500 r / min for 1-5 s, then 2500-3000 r / min for 55-60 s;
[0020] (2) Dry the graphene / copper foil spin-coated with PMMA;
[0021] (3) Remove the area of the copper foil substrate that is not spin-coated with PMMA to obtain PMMA / graphene / copper foil;
[0022] (4) Immerse PMMA / graphene / copper foil in FeCl3 solution until the copper foil is completely etched away and PMMA / graphene is completely detached to obtain PMMA / graphene.
[0023] The concentration of the FeCl3 solution is 0.1–0.5 mol / L; the etching time is 24–72 h.
[0024] (5) Soak PMMA / graphene in deionized water for cleaning;
[0025] (6) The cleaned PMMA / graphene is laid on the second substrate and allowed to dry naturally;
[0026] (7) Heat the second substrate with PMMA / graphene obtained in the previous step at 55-65°C for 20-30 minutes to bond PMMA / graphene with the second substrate.
[0027] (8) After the product obtained in the previous step has cooled naturally, soak it in acetone to wash away the PMMA.
[0028] (9) After soaking in acetone, soak in isopropanol, and finally take it out and blow it dry with nitrogen to obtain the graphene film transferred to the second substrate.
[0029] The material of the second substrate is Si / SiO2, TPU or PET.
[0030] The essential features of this invention are:
[0031] In this invention, copper foil is first melted at 1100℃~1200℃, and then graphene is grown on the liquid copper foil substrate by chemical vapor deposition.
[0032] This invention involves holding the copper foil under high-temperature annealing for a period of time. This is because the copper foil has just melted into liquid copper. If methane were directly introduced at this point for graphene growth, the graphene lattice would have many defects due to the large number of grain boundaries, steps, and other rough areas present in the copper foil. By maintaining a constant growth temperature and first performing annealing, the copper foil completely melts into liquid copper. Introducing methane then significantly reduces the number of defects in the graphene lattice. Furthermore, annealing promotes the interaction and bonding between graphene and the liquid copper substrate, thereby improving the adhesion and stability of graphene on the liquid copper surface. This effectively enhances the quality and performance of the graphene, making it more suitable for practical applications.
[0033] Due to the unique "self-limiting growth" mechanism of copper foil substrates, large-area graphene can be easily obtained on copper foil substrates. By adjusting the gas flow rate, growth temperature and growth time, large-area, low-layer, high-quality graphene films can be obtained on the surface of liquid copper foil. Moreover, the graphene films can be prepared in a short time and achieve atomic-level flatness, which provides a methodological prerequisite for growing high-quality graphene films.
[0034] Secondly, graphene's unique lattice and band structure endow it with many excellent properties, such as high carrier mobility, ultra-high electrical conductivity, and excellent thermal and optical properties. Therefore, graphene can be used to design various stable optoelectronic devices and fabricate a variety of van der Waals heterostructures. This invention utilizes a wet transfer technique to peel graphene films from a substrate and transfer them to a substrate more suitable for a specific application.
[0035] The beneficial effects of this invention are as follows:
[0036] Excellent crystal quality: Chemical vapor deposition (CVD) can produce high-quality graphene crystals on liquid copper. Liquid copper, as a substrate, provides uniform heat transfer and a stable environment, which helps graphene form larger crystal particles and fewer defects during growth, thus improving the crystal quality of the graphene.
[0037] Good mechanical stability: The overall structure of few-layer, large-area graphene prepared on liquid copper foil substrate is relatively stable, which helps to improve the mechanical properties and long-term stability of graphene, making it more suitable for flexible electronic devices and other fields.
[0038] Highly controllable: The morphology, thickness, and crystal shape of graphene can be controlled by adjusting growth conditions such as growth temperature, growth time, and the flow rate of the hydrogen-argon mixture.
[0039] Reducing substrate surface treatment: When growing graphene on solid copper, in order to improve the quality of the grown graphene, in addition to removing surface impurities with acetone and isopropanol, electrochemical polishing is also required to achieve a smooth surface. By increasing the temperature, the copper foil is melted into liquid copper. Utilizing the quasi-smooth and rheological surface of liquid copper eliminates the cumbersome electrochemical polishing step and results in higher quality graphene. Attached Figure Description
[0040] Figure 1 This is a schematic diagram of the chemical vapor deposition growth of graphene used in an embodiment of the present invention;
[0041] Figure 2 This is a diagram illustrating the growth process of the chemical vapor deposition graphene used in Example 1.
[0042] Figure 3 This is an optical microscope image of few-layer graphene grown on a liquid copper foil substrate. Figure 3 (a) is an optical microscope image of the few-layer graphene grown in Example 1. Figure 3 (b) is an optical microscope image of the multilayer graphene grown in Comparative Example 3. Figure 3 (c) is an optical microscope image of the graphene after oxidation in Comparative Example 1;
[0043] Figure 4 This is an optical microscope image of graphene grown on a solid copper substrate in Comparative Example 2.
[0044] Figure 5 This is a Raman image of few-layer graphene grown on a copper foil substrate in Example 1;
[0045] Figure 6 The image shows the characterization of transferred graphene in Example 1. Figure 6 (a) is an optical microscope image of graphene transferred onto a copper foil. Figure 6 (b) is a scanning electron microscope image of graphene transferred onto copper foil. Figure 6 (c) Raman image of graphene transferred on copper foil;
[0046] Figure 7 This is a schematic diagram of the wet transfer of graphene films. Detailed Implementation
[0047] To better understand the present invention, the following examples further illustrate the chemical vapor deposition growth of few-layer graphene films of the present invention. However, the scope of protection of the present invention is not limited to the scope shown in the examples.
[0048] Example 1
[0049] This embodiment discloses a method for preparing few-layer, large-area graphene films, specifically including the following steps:
[0050] S1. Cut copper foil (250μm) and tungsten foil into 1×1cm squares and flatten them. Clean them ultrasonically for 10 minutes each in acetone, ethanol, and deionized water to remove contaminants from the substrate surface, then dry them with nitrogen gas.
[0051] S2. Place the copper foil on the tungsten foil, put both into the quartz boat, push them into the heating zone of the tube furnace and evacuate to 8.5E-1Pa;
[0052] S3. Control the heating time for 65 minutes, grow the temperature to 1100℃, keep the temperature at 1100℃ during the annealing stage, anneal for 30 minutes, and introduce two gases during this period, of which the flow rate of H2 / Ar (volume ratio of 1:1) is 50 sccm, and the flow rate of argon gas alone is 150 sccm.
[0053] S4. During the growth process, the temperature is maintained at 1100℃. CH4 gas is introduced at a flow rate of 5 sccm.
[0054] S5. Maintain the temperature and allow the growth time to reach 40 minutes.
[0055] S6. After growth is complete, the methane gas is turned off and the system is allowed to cool naturally to room temperature. A few layers of large-area graphene film can be obtained on a copper foil substrate.
[0056] Example 2
[0057] The difference between this embodiment and Embodiment 1 is that the growth time in S5 is changed to 60 min to obtain the sample to be tested.
[0058] Example 3
[0059] The difference between this embodiment and Embodiment 1 is that the CH4 flow rate in S4 is changed to 1 sccm to obtain the sample to be tested.
[0060] Example 4
[0061] The difference between this embodiment and Embodiment 1 is that the CH4 flow rate in step S4 is changed to 1 sccm, and the growth time in step S5 is changed to 20 min, thus obtaining the sample to be tested.
[0062] Example 5
[0063] This embodiment discloses a method for transferring graphene thin films:
[0064] S1. Use tape to fix the four sides of the upper surface of the copper foil substrate with graphene in Example 1 to the cover glass.
[0065] S2. Place the sample in the spin coater and secure it with tape. Drop PMMA solution onto the sample surface, then rotate the spin coater to evenly distribute the PMMA. The spin coater parameters are 1500 r / min for 5 seconds, then 2500 r / min for 55 seconds.
[0066] S3. Remove the sample, remove the tape, and allow the PMMA-coated graphene / copper foil sample to air dry naturally in a fume hood.
[0067] S4. After the sample has dried, cut off the area around the copper foil substrate that was covered with tape but not spin-coated with PMMA.
[0068] S5. Prepare a 0.1 mol / L FeCl3 solution and immerse the PMMA / graphene / copper foil sample in the solution for 50 hours until the copper foil is completely etched away and the PMMA / graphene film floats on the surface of the solution.
[0069] S6. Gently lift the PMMA / graphene sample with a coverslip and place it in deionized water. Transfer it multiple times in deionized water to thoroughly wash away any residual FeCl3 solution.
[0070] S7. Using a new, cleaned Si / SiO2 substrate, remove the clean PMMA / graphene sample from the deionized water and allow it to air dry naturally.
[0071] S8. Place the sample on the heating stage and heat at 60°C for 30 minutes to make the PMMA / graphene film adhere more tightly to the substrate.
[0072] S9. After the sample has cooled, place it in acetone and soak for 90 minutes to remove PMMA. Change the acetone every 30 minutes to wash away the PMMA. Note that when changing the acetone, leave a small amount of acetone to cover the sample surface to prevent the acetone from completely evaporating and leaving organic matter or other impurities on the sample surface.
[0073] S10. After soaking in acetone, soak the sample in isopropanol for 45 minutes to remove the acetone. Replace the isopropanol every 15 minutes. Finally, take out the sample and dry it with nitrogen to obtain a clean graphene film sample that has been transferred.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that the graphene grown in Example 1 was placed on a baking machine, the temperature was set to 200°C, and baked for 30 minutes.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the temperature in S3 and S4 is changed to 900°C to obtain the sample to be tested.
[0078] Comparative Example 3
[0079] The difference between this embodiment and Embodiment 1 is that the CH4 flow rate in S4 is changed to 10 sccm to obtain the sample to be tested.
[0080] The samples from the above 6 embodiments and 2 comparative examples were observed under an optical microscope to preliminarily determine their surface morphology characteristics. The morphology was further characterized by scanning electron microscopy, and the number and quality of graphene layers were characterized by Raman spectroscopy.
[0081] Figure 1 This is a schematic diagram of chemical vapor deposition for growing graphene. Copper foil is used as the growth substrate, tungsten foil is used as the support substrate, the carrier gas is a mixture of hydrogen and argon and pure argon, the carbon source for growth is methane, and the temperature is raised to the melting temperature of copper foil to achieve the preparation of graphene on liquid copper.
[0082] Figure 2 This is a diagram illustrating the growth process of the chemical vapor deposition graphene used in Example 1. Figure 2 It can be clearly seen that the growth temperature of graphene is 1100℃. Since the melting point of copper foil is 1084℃, the copper foil has melted into liquid when graphene is grown at 1100℃. The quasi-smoothness and rheological surface of liquid copper make the prepared graphene layers more uniform and of higher quality.
[0083] Figure 3 This is an optical microscope image of few-layer graphene grown on a copper foil substrate in Example 1. Figure 3 As shown in (a), the copper foil surface is uniform and smooth, indicating that copper foil liquefaction is indeed beneficial for graphene growth. However, due to the transparent color of graphene and the fact that few-layer graphene does not have the island-like shape of multi-layer graphene, it is difficult to achieve the desired growth. Figure 3 As shown in (b), it is not possible to visually demonstrate the graphene coating on the copper foil surface under light. Comparative Example 1 involves oxidizing the graphene grown in Example 1 at 200°C for 30 minutes, followed by observation under an optical microscope. Figure 3 As shown in (c), fine, light red cracks were found. The cracks were caused by the thermal expansion of the copper foil during heating, which tore the film. The torn parts did not cover the copper foil, and after oxidation, fine, light red oxide parts were formed. The small clusters of cracks also indirectly indicate that the grown graphene is relatively thin, while the parts that did not change color also indirectly indicate that they were covered by graphene. Comparative Example 1 shows that Example 1 grew a large-area, few-layer graphene.
[0084] Figure 4The image shown is an optical microscope image of the graphene grown on the surface of a solid copper foil at 900℃ after oxidation, as described in Comparative Example 2. The image reveals severe oxidation of the copper foil surface, with almost no graphene coverage. This is because the solid copper foil surface contains numerous rough areas such as grain boundaries and steps, resulting in low-quality graphene grains, small size, and uneven layer count.
[0085] Figure 5 This is a Raman image of few-layer graphene grown on a copper foil substrate in Example 1. The Raman image clearly shows the growth at 1580 cm⁻¹. -1 and 2687cm -1 The vicinity contains both G-peaks and 2D-peaks of graphene, and the intensities of the G-peaks and 2D-peaks are comparable. Based on relevant data or literature, it can be concluded that the grown graphene is a bilayer graphene, and that the peak intensity is at 1350 cm⁻¹. -1 No obvious D peak (defect peak of graphene) was found nearby, indicating that the graphene grown on the copper foil substrate has a complete structure and good performance. In the Raman spectrum, in addition to the characteristic peak of graphene, very weak characteristic peaks of graphene were also found, and there were many impurity peaks in addition to the characteristic peaks. This is because the copper foil surface interferes with the measurement, rather than because the grown graphene has defects.
[0086] Figure 6 The image shows the characterization of transferred graphene in Example 1. Figure 6 (a) is an optical microscope image of graphene transferred onto a copper foil. Figure 6 (b) is a scanning electron microscope image of graphene transferred onto copper foil. Figure 6 (c) Raman plot of graphene transferred onto copper foil, from Figure 6 As shown in (a), the transferred graphene film is darker in color than the Si / SiO2 substrate, indicating that the film was indeed visibly transferred to the Si / SiO2 substrate. However, some colored impurities were also found on the graphene film. This is likely due to residual FeCl3 solution not being completely removed during the transfer process. Figure 6 (b) shows the film fragments after transfer more clearly, and Raman characterization was performed. From Figure 6 The Raman graph in (c) clearly shows that at 1580 cm⁻¹ -1 and 2687cm -1 The vicinity contains both G-peaks and 2D-peaks of graphene, and the intensities of the G-peaks and 2D-peaks are comparable. Based on relevant data or literature, it can be concluded that the grown graphene is a bilayer graphene, and that the peak intensity is at 1350 cm⁻¹. -1 No obvious D peak (defect peak of graphene) was found in the vicinity, indicating that the transferred graphene has a complete structure and good performance.
[0087] Figure 7This is a schematic diagram of graphene wet transfer. The present invention utilizes graphene wet transfer technology to peel graphene films from a substrate and transfer them to a substrate more suitable for a specific application, such as TPU or PET.
[0088] Matters not covered in this invention are common knowledge.
Claims
1. A method for preparing few-layer, large-area graphene by chemical vapor deposition, characterized in that the method includes the following steps: S1. Clean the copper foil and tungsten foil with acetone, ethanol and deionized water respectively for 10-20 min, and then dry them with nitrogen gas. S2. Place the copper foil on the tungsten foil, put both into the quartz boat, push them into the heating zone of the tube furnace, and evacuate to 9~8.5E-1Pa; S3. Anneal at 1100℃~1200℃ in a mixed atmosphere, and hold the temperature for annealing for 30~40 minutes. S4. Maintaining the atmosphere and temperature of the previous step, introduce CH4 gas into the tube furnace for 10~90 minutes; then turn off the CH4 gas and allow it to cool naturally to room temperature to obtain a few-layer graphene film on the copper foil substrate. The heating time is 65 minutes; The mixed atmosphere is hydrogen and argon, with a volume ratio of hydrogen to argon of 5~50:100~200. The area of the graphene film is 0.25 cm². 2 ~1cm 2 ; The thickness of the copper foil substrate described in S1 is 250μm~300μm; The number of layers mentioned refers to 1 to 3 layers.
Citation Information
Patent Citations
Loss-less transfer method for large-size graphene
CN102897759A
Method for preparing wrinkle-free graphene film
CN112707389A
